Integration of Islam and Science in Physics Learning: A Case Study of The First Law of Thermodynamics - Meiliyadi, Lalu Ahmad Didik; Arizona, Kurniawan; Efendi, M. Harja; Wahyudi, Muh.; Damayanti, Isniwana (Universitas Islam Negeri (UIN) Mataram, 2025)
There is a strong belief in society that religion and science are two entities that cannot be reconciled. They are separate from one another and have their domains. Integration is the keyword for discussing the relationship between science and religion. The integration of science and religion can be achieved by taking the philosophical core of fundamental Islamic religious sciences as a paradigm for future science. This integration process can be seen as the Islamisation of science as part of the Islamisation of civilization. One example of this integration can be seen when discussing one branch of science, namely physics, about Islamic studies. In this case, one topic is taken from the First Law of Thermodynamics. Thermodynamics is the science that discusses heat and its changes. Heat and its changes have been explained in the Qur'an, as stated in the words of Allah SWT in Surat Al-A'raf, verse 52. For example, the source of heat energy has been explained in Surat Yaasin, verse 80, and Surat Yunus, verse 5, which state that fire is the source of heat. In its transformations, according to the First Law of Thermodynamics, this heat energy can change into changes in internal energy and work. Changes in internal energy occur due to an increase in the system's temperature after heat energy is added, while work arises due to a change in the system's volume after heat energy is added. As an illustration of the First Law of Thermodynamics, let us imagine a balloon. If the balloon is heated, the air particles inside the balloon will experience an increase in temperature. It is the nature of a particle that when its temperature increases, its energy also increases. This increase in energy is what we call an increase in internal energy. Since the internal energy of the gas particles inside the balloon increases, there will be more energy for the gas particles inside the balloon to move and collide with the walls of the balloon. As a result, the volume of the balloon will increase, and work will be done. If the elasticity of the balloon can no longer withstand the collisions of the gas particles inside it, the balloon will burst.